2016
DOI: 10.3109/02699052.2016.1147602
|View full text |Cite
|
Sign up to set email alerts
|

Narrative skills of children treated for brain tumours: The impact of tumour and treatment related variables on microstructure and macrostructure

Abstract: Preliminary findings highlight the importance of investigating narrative abilities as part of a comprehensive language assessment. Macrostructure should be routinely examined where children are diagnosed with either posterior fossa tumour or hydrocephalus or have undergone surgery and/or chemotherapy for brain tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
0
18
1
Order By: Relevance
“…Language difficulties ranging in severity and impact were reported in children with CBTL, including problems with general language (eg, vocabulary, syntax), 22–26,34–36,54–57,62,65,68,73–77 specific word‐finding difficulties, 24,54,68 narrative skills, 78 and high‐level language difficulties (eg, metaphors, ambiguity, figurative language) 23,25,26,76,77,79,80 . Literacy skills including preliteracy, reading, writing, and spelling were also identified as areas of weakness in several studies, 23,27,29,35,65,79,81 although one study showed intact reading decoding for children receiving treatment for brain tumor 82 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Language difficulties ranging in severity and impact were reported in children with CBTL, including problems with general language (eg, vocabulary, syntax), 22–26,34–36,54–57,62,65,68,73–77 specific word‐finding difficulties, 24,54,68 narrative skills, 78 and high‐level language difficulties (eg, metaphors, ambiguity, figurative language) 23,25,26,76,77,79,80 . Literacy skills including preliteracy, reading, writing, and spelling were also identified as areas of weakness in several studies, 23,27,29,35,65,79,81 although one study showed intact reading decoding for children receiving treatment for brain tumor 82 …”
Section: Resultsmentioning
confidence: 99%
“…A number of studies on language outcomes included between‐group comparisons with a typically developing control group and found no statistically significant differences between groups on some or all measures 25,26,28,69,74,75,77–79,83–85 . However, the ability to interpret group‐level comparisons was often limited due to small sample sizes for the CBTL group (≤17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deficits in high-level language skills, such as the ability to interpret a respond to a conversation, have been identified in children with tumour in the right cerebellum 17 . In this vein, a focus on the narrative skills of children with brain cancer has been recommended 18 .…”
Section: Introductionmentioning
confidence: 99%